The Affecting Factors of School Readiness for Implementing the Merdeka Belajar Policy - Rusdinal; Ranti Meizatri; Rifma (Jurnal Pendidikan Indonesia, 2024)
This research analyzes the factors influencing schools' readiness to implement the independent learning policy. This research was conducted using a mixed-method approach. Sampling was conducted proportionally from 30 public and private junior high schools in Padang City, Indonesia. So, the participants in this research consisted of 30 school principals, 207 teachers, and 63 staff. Data analysis was carried out using SEM intelligent PLS. The relationship between variables is analyzed by referring to the original sample values and T-statistic output from Smart PLS. The research results show the factors that influence schools' readiness to implement the independent learning policy; first, the knowledge dimension consists of knowledge to change, initiative to change, responsibility to change, and creativity to change with a t-statistic of 34.012. Second, the attitude dimension consists of the need to change, commitment to change, and belief in change, with a t-statistic of 42.680. Third, the institutional dimension consists of making changes, personal involvement, changing ideas/programs, supporting resources, and collaboration with a t-statistic of 38.454. It is concluded that understanding, a positive attitude toward change, and solid institutional support are critical factors in increasing school readiness in implementing the independent learning policy. The implication of this research is the importance of developing training and education programs that focus on increasing knowledge, attitudes, and institutional support to facilitate the implementation of independent learning policies in schools.